State of the Union Addresses - Bush, George, 1924-2018 (Salt Lake City, UT : Project Gutenberg, 2004)
"State of the Union Addresses by George H.W. Bush" is a collection of presidential addresses delivered by George H.W. Bush during the early 1990s. This book includes his speeches given on January 31, 1990, January 29, 1991, and January 28, 1992. As a historical publication, it provides insight into significant political thoughts and national issues during a transformative period in American history, post-Cold War and amid geopolitical shifts, with an emphasis on freedom, democracy, and economic challenges. In these addresses, Bush reflects on the state of the nation and its role on the global stage, particularly in light of the dramatic political changes in Eastern Europe and the ongoing conflict in the Persian Gulf. He speaks about the importance of maintaining American ideals of democracy and freedom, the need for economic revitalization through investments in education and human capital, and his commitment to foreign alliances and national defense. The speeches convey a message of optimism, urging cooperation among Americans while addressing pressing issues such as crime, education reform, and healthcare, ultimately emphasizing a shared American purpose in achieving progress and securing a peaceful future for generations to come. (This is an automatically generated summary.)
Release date is 2004-02-01
Produced by James Linden. HTML version by Al Haines.
Keywords: Presidents -- United States -- Messages; United States -- Politics and government -- Sources